2000
DOI: 10.1111/j.0065-1591.2000.acp29-03.x
|View full text |Cite
|
Sign up to set email alerts
|

Why do people with anxiety disorders become depressed? A prospective‐longitudinal community study

Abstract: Objective: To examine the temporal relationships of anxiety and depressive disorders, their risk factors and to explore why people with anxiety develop depression. Method: Data from an original 4±5-year prospective-longitudinal community study (N=3021) of adolescents and young adults with DSM-IV anxiety and depressive disorders identi®ed with the Composite International Diagnostic Interview are used to examine risk factors, as well as course and outcome. Results: (i) Anxiety disorders, except for panic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
213
3
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(247 citation statements)
references
References 13 publications
(18 reference statements)
21
213
3
10
Order By: Relevance
“…This suggests low potency to be primarily associated with offspring anxiety and offspring comorbid anxiety and depression, possibly because low child potency hampers the development of mastery and control beliefs and thus promotes anxiety. Our result that low potency was associated with offspring depression in separate models only may be explained by the possibility that many individuals developed anxiety first and depression secondary to anxiety [11,[70][71][72][73]. Our findings with respect to potency match with previous evidence for conceptually related constructs (low child autonomy, low maternal autonomy granting, high maternal intrusiveness) to be primarily associated with offspring anxiety symptoms [35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…This suggests low potency to be primarily associated with offspring anxiety and offspring comorbid anxiety and depression, possibly because low child potency hampers the development of mastery and control beliefs and thus promotes anxiety. Our result that low potency was associated with offspring depression in separate models only may be explained by the possibility that many individuals developed anxiety first and depression secondary to anxiety [11,[70][71][72][73]. Our findings with respect to potency match with previous evidence for conceptually related constructs (low child autonomy, low maternal autonomy granting, high maternal intrusiveness) to be primarily associated with offspring anxiety symptoms [35][36][37][38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…In line with studies that revealed anxiety disorders as important risk factors for secondary depression Sutter-Dallay et al, 2004;Wittchen et al, 2000) the present study also showed that women with pure A prior to pregnancy had a sevenfold risk for incident depressive disorders as compared to women with no AD (OR¼7.2, 95%CI: 1.5-34.0, p¼0.012). The OR for the association of pure D prior to pregnancy and incident anxiety disorders failed to reach significance.…”
Section: Tablesupporting
confidence: 90%
“…Only one study specifically examined anxiety and depression scores in that population: Laggari et al (11) used the StateTrait Anxiety Inventory to screen subjects and, after controlling for age, socioeconomic status, and stressful life events, reported a slight increase in anxiety scores in PCOS girls (OR 1.08, 95% CI 1.003-1.17). Given that anxiety is a chronic recurring disorder, it has been suggested that appropriate evaluation and treatment of anxiety symptoms at an early age may prevent the onset of secondary disorders (18). Some authors have suggested that adolescents with PCOS are at a higher risk for anxiety symptoms likely related to the clinical signs of hyperandrogenism.…”
Section: Discussionmentioning
confidence: 99%